(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article mentions the emergence of global environmental and social problems today and their economic consequences. It is also necessary to develop the green economy, create an ESG system in banks, assess and manage environmental and social risks.